The effects of extra-familial child sexual abuse on the victim's primary care givers - Mashiloane, Salome Mamphoreng (My University, 2006)
This study explored the effects of extra-familial child sexual abuse on the victims’ primary caregivers. The study focused on the experiences of ten mothers whose children were raped during the six months that preceded the study, and they were drawn from Zamokuhle and Nthabiseng clinics in Soweto. A semi-structured individual interview was used to explore the implications of the rape on the primary caregivers’ psychological well being. The data was processed using qualitative content analysis as the methodology. Findings indicate that the children were raped in their everyday environment during their mothers’ absence. The majority of the perpetrators are trusted neighbours and some used violence to coerce the children into participating. Some children concealed the rapes from their mothers and they were threatened with punishment to facilitate disclosure. The primary caregivers responded with anger post-disclosure which was directed toward different parties. They blamed the children for withholding the rape and for failing to combat it, and the perpetrators for betraying them. The mothers’ anger was exacerbated by the failure of the justice system to bring the perpetrators to book, and other people whom the mothers felt should have protected their children. In terms of causal attribution, the respondents questioned their maternal role and felt that they did not provide their children with the necessary care and protection they needed. The primary caregivers also felt that the children could have prevented the rape if they behaved differently. The rape took a toll on the relationship the mothers had with their children as some became overprotective to compensate for the protection they never provided their children with. Most mothers displayed an inability to cope post-disclosure which suggests that child sexual abuse has adverse effects on the psychological well-being of noniv offending mothers. For purposes of clarity, the word “mother” will be used interchangeably with “primary caregiver” throughout the study.
Faculty of Humanities School of Human and Community Development 0008716g Mashils@hotmail.com
Keywords: Child sexual abuse; victims parents; Victims of rape; Extra-familial; Victims caregivers